PENDEKATAN AFEKTIF GURU AQIDAH AKHLAK DALAM MEMBENTUK KARAKTER POSITIF SISWA UNTUK MENCEGAH BULLYING DI MA AL ISLAMIYAH - Muhammad Fathan Jamil (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
The affective approach of Aqidah Akhlak teachers plays an important role in shaping positive character in students and preventing bullying. Through role modeling, empathy, emotional connection, and personal guidance, values such as compassion, fairness, and mutual respect can be internalized in a meaningful way. This approach is effective when supported by a conducive school culture and collaboration among all members of the school community. This study concludes that the descriptive qualitative approach is effective in exploring in depth the affective approach of Aqidah Akhlak teachers in shaping positive student character and preventing bullying. Through interviews, observations, documentation, interactive data analysis, and triangulation, this study produced a valid, contextual, and meaningful empirical picture. The affective approach in Aqidah Akhlak learning has been proven effective in shaping students' positive character and preventing bullying. Through the internalization of values, teacher role modeling, habit formation, and good emotional relationships, students show an increase in empathy and mutual respect. This approach has an impact on changing student behavior and creating a more conducive classroom climate. The affective approach of Aqidah Akhlak teachers at MA Al Islamiyah plays an effective role in shaping positive character and preventing bullying. Through role modeling, habit formation, and good emotional relationships, students show increased empathy and mutual respect The success of this approach is supported by teacher consistency, a conducive school culture, and parental cooperation.